Serum sickness reaction to obinutuzumab in a patient with chronic lymphocytic leukaemia. Issue 12 (22nd December 2021) - Elmanaseer, Oday; Avelino, Alzira R M; Azem, Amin; Raval, Mihir
Abstract : Serum sickness (SS) is a known phenomenon; however, it is commonly missed due to vague symptoms, and is usually confounded by other aetiologies that present similarly. Obinutuzumab is a novel anti-CD20 antibody agent that has been approved for chronic lymphocytic leukaemia (CLL) treatment. At the time of approval, it was not linked to SS; however, this phenomenon has been recognised with other anti-CD20 agents like rituximab. SS remains a rare entity, but it is important to be recognised accurately and quickly in the appropriate circumstances, so that effective treatment with corticosteroids can be initiated to alleviate inflammatory symptoms. Here we present a patient with CLL who developed maculopapular rash, fever and polyarthritis and elevated inflammatory markers consistent with serum sickness triggered by obinutuzumab and was effectively treated with corticosteroids.